Introducing: Computational Science - Maxville, Valerie (Elsevier, 2013)
A deep understanding of computational science takes years to develop, however a basic grasp can be achieved in a short workshop. This can create and nurture the spark of interest in computational approaches to solving science problems. A series of outreach activities has been developed for this purpose at iVEC in Western Australia. The activities include simulation and analogy to give an accessible introduction to computational science and supercomputing concepts. This paper describes the developed lesson plans and reflects on the results of delivering workshops to a range of audiences.